1983
DOI: 10.1128/iai.42.3.1049-1054.1983
|View full text |Cite
|
Sign up to set email alerts
|

Induction of interleukin 1 secretion by adjuvant-active peptidoglycans

Abstract: The ability of differently structured, purified peptidoglycans (PG) to induce interleukin 1 (IL1) secretion was compared. PG from Bacillus megaterium and Staphylococcus aureus stimulated the production of IL1 by mouse peritoneal macrophages and human adherent mononuclear cells, whereas PG from Micrococcus lysodeikticus and Corynebacterium poinsettiae were inactive. There was a correlation between the ability of PG to induce IL1 secretion and previously demonstrated immunoenhancing activities (adjuvant effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Activated macrophages play an important role in defense mechanisms against foreign materials (8,20,37). The activation of macrophages can be measured by an increase in tumorcidal or bactericidal activity, enhancement of glucosamine incorporation into the cells, glucose oxidation and superoxide anion generation or production of tumor necrosis factor and interleukin-1 (15,17,19,20,31,37,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated macrophages play an important role in defense mechanisms against foreign materials (8,20,37). The activation of macrophages can be measured by an increase in tumorcidal or bactericidal activity, enhancement of glucosamine incorporation into the cells, glucose oxidation and superoxide anion generation or production of tumor necrosis factor and interleukin-1 (15,17,19,20,31,37,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…While MDP has been shown to stimulate guinea pig peritoneal exudate macrophages in vitro without the involvement of lymphocytes (33)(34)(35)52), there are conflicting reports in the literature on the stimulation of murine macrophages by MDP. Some investigators have, on the basis of in vitro assay results, reported that murine macrophages are the initial target cells of MDP (11,16,18,38,48,49,51), while others have failed to show in vitro activation of murine macrophages by MDP (30,45,53).…”
mentioning
confidence: 99%
“…IL-1 production was assayed with peritoneal macrophages of C3H/HeN mice after induction with 10% (w/v) trypticase peptone (BBL; Microbiology Systems, Cockeysville, MD). IL-I production was determined by measuring C3H/HeJ mouse thymocyte proliferation in the presence of a suboptimal dose of phytohaemagglutinin (PHA; Wellcome Diagnostics, Dartford, U.K.) according to the method of Vacheron et al [14].…”
Section: Interleukin-1 Assaymentioning
confidence: 99%
“…In vitro, IL-1 upregulates the activity of T helper cells, possibly influencing the balance between different subsets [2,9]. Adjuvants such as lipopolysaccharide (LPS), muramyl dipeptide (MDP) and cholera toxin (CT) are shown to stimulate macrophages in vitro to produce IL-1, which is therefore considered to be an important factor in their adjuvant activity [10,11]. With respect to other adjuvants such as Freund's complete adjuvant, Freund's incomplete adjuvant and alum, IL-1 seems to play a limited role, if any, as an enhancer of the primary immune response [12].…”
Section: Introductionmentioning
confidence: 99%